An Anomaly Detection Technique for Deception Attacks in Industrial Control Systems - Qassim Q.; Ahmad A.R.; Ismail R.; Abu Bakar A.; Abdul Rahim F.; Mokhtar M.Z.; Ramli R.; Mohd Yusof B.; Mahdi M.N. (Institute of Electrical and Electronics Engineers Inc., 2023)
Anomaly detection; Big data; Commercial off-the-shelf; Computer crime; Intrusion detection; Learning systems; Network security; SCADA systems; Terrorism; Catastrophic consequences; Commercial off-the-shelf products; Deception Attack; Industrial control systems; Intrusion Detection Systems; Intrusion detection technologies; National infrastructure; SCADA; Intelligent control